Characteristics of methanogens isolated from bovine rumen. - Miller, T L (1986)
Six strains of methanogens were isolated from 10(-8) and 10(-9) ml of bovine rumen contents. All strains had the morphologic and physiologic characteristics of Methanobrevibacter spp. Four strains required coenzyme M; two did not. Growth of all strains either depended on or was stimulated by a mixture of isobutyric, isovaleric, 2-methylbutyric, and valeric acids. None of the strains reacted with antiserum against the type strain of Methanobrevibacter ruminantium.